2019
DOI: 10.1039/c9cp04741g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water on the stochastic motions of propane confined in MCM-41-S pores

Abstract: Quasi-elastic neutron scattering (QENS) and molecular dynamics simulations (MDS) reveal the effects of water on the structure and dynamics of propane confined in 1.5 nm wide cylindrical pores of MCM-41-S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…These results confirm that the presence of water strongly impedes the transport of propane across the hydrated pores, in qualitative agreement with prior simulations, and also with expectations. A similar damping of propane mobility due to presence of D 2 O in MCM-41-S has also been observed in quasielastic neutron scattering experiments . Unfortunately, only a qualitative comparison can be made, because the experiments were conducted at lower temperatures than the simulations presented here.…”
Section: Simulation Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…These results confirm that the presence of water strongly impedes the transport of propane across the hydrated pores, in qualitative agreement with prior simulations, and also with expectations. A similar damping of propane mobility due to presence of D 2 O in MCM-41-S has also been observed in quasielastic neutron scattering experiments . Unfortunately, only a qualitative comparison can be made, because the experiments were conducted at lower temperatures than the simulations presented here.…”
Section: Simulation Resultssupporting
confidence: 73%
“…A similar damping of propane mobility due to presence of D 2 O in MCM-41-S has also been observed in quasielastic neutron scattering experiments. 31 Unfortunately, only a qualitative comparison can be made, because the experiments were conducted at lower temperatures than the simulations presented here.…”
Section: Simulation Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The role of water on propane diffusion in silica nanopores was recently discussed in detail, in which molecular dynamics simulations and QENS (quasielastic neutron scattering) were used to reveal that water restricts propane motion and self-diffusion at high loadings. , The silica nanopores in that work were smaller than the 10 nm average pore size used here, i.e., 1.6 nm, and results indicated that propane became entrapped by water in the center of the pores, not near the walls. It is not possible to rule out that cyclohexane may also become entrapped by water at positions away from the pore wall, contrary to what is depicted in Figure .…”
Section: Resultsmentioning
confidence: 76%